Analysis of application of key performance indicator with SMART-C - Ade Irma Sagala (International Journal on Social Science, Economics and Art, 2022)
The utilization of key performance indicators refers to the utilization of indicators that have distinctive characteristics, characteristics of measurement that can show changes that occur in a particular field so that the work result in quality and quantity achieved by a person in the course of carrying out their responsibilities are in accordance with the responsibilities that have been assigned. However, the application of this is not yet at its most effective for all of the workers of PT. Multi Jaya Samudera. The objective of this study is to conduct an investigation into the utilization of key performance indicators (KPI) with smart-c. The descriptive qualitative methodology was used for this investigation. The findings of the study require the management to make a commitment to implementing key performance indicators that are in accordance with smart-c and to paying attention to the vision and mission of the company in addition to the targets that are set forth in the management contract each year. This is done so that employees can make a measurable contribution to the implementation of key preformance indicators assessments.